Beer and Taxes: The Fiscal Significance for Holland and England in the Seventeenth and Eighteenth Centuries - Unger, Richard W. (TSEG - The Low Countries Journal of Social and Economic History, 2022)
Beer taxes were long a significant source of government revenue in northern Europe. In Holland the income from beer taxes went into long-term decline from 1650 onward. In England the take remained more stable. In both, beer produced a falling share of total revenue as expenses increased in an era of frequent and increasingly costly wars. The fiscal policies pursued in reaction to beer contributing a declining share of total government income led, by 1800, to policies that made the tax burden more broadly shared in the Netherlands than it was in Great Britain. The failure of beer to support the states, as the drink had previously, was less important to fiscal health than more general developments in population and in the economies of the two.